Fabrication of Advanced Nanohybrid Materials and Their Deployment in Electrochemical Sensing of Diverse Analytes - Singh N.; Azad U.P.; Srivastava A.; Kumari R.; Prasad R.; Chandra P. (My University, 2025)
The term “nanohybrid” materials refers to materials made of artificial organic and inorganic components joined at the nanoscale level in a covalent or non-covalent way. The contribution of the inorganic groups, that act as functional groups raises the chemical reactivity of the organic basis material. At the vanguard of a new discipline that combines material science, biology, and nanotechnology is the creation of these novel materials. This is an interdisciplinary subject that is at the forefront of technological development. The hybrid material’s remarkable multifunctionality is enhanced by its nanoscale size, structure, shape, and surface chemistry. In recent years, electrochemical biosensor design has evolved to include a range of nanohybrid materials (NHMs) for target analyte detection. Electrochemical biosensors based on NHMs provide better analytical performance in terms of fast reaction times, reasonably priced transducer surface designs, and extended stability. This chapter focuses on the fabrication of several advanced nanohybrid materials and their implementation in the electrochemical sensing of diverse analytes. Potential directions for future research include investigating novel materials to create a new and smart nanohybrid materials-based platform with unique and remarkable features. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.